Internalisasi Nilai Pendidikan Sosial dalam Membina Karakter Santri - Fahrurrazi, Fahrurrazi (Saree: Research in Gender Studies, 2021)
This research uses qualitative approach, because in this study tried to study phenomenology in an atmosphere that takes place naturally and naturally, not in controlled conditions. This research instrument is the researcher himself (human instrument/main tool) in addition researchers also bring other tools in the form of mobile phones, digital cameras. Other instruments include interview guidelines, observation guidelines and documentation guidelines. The result of fostering children's character in dayah is done through approach with individuals by getting used to establishing friendship because the role of dayah first in coaching ukhuwah is through the upbringing of santri-santri who shelter in the dayah because of the bad state of santri in adulthood depending on the education received in childhood if the mother instills ukhuwah, mutual respect, manners between each other love and be honest.